A practical guide for policy analysis the eightfold path to more effective problem solving - Bardach, Eugene; Patashnik, Eric M. (Sage, 2024)
"This handbook serves as a guide to concepts and methods applied in the analysis of policy. Eugene Bardach developed the general approach and many of the specific suggestions over thirty-five years of teaching policy analysis workshops to first- and second-year graduate students at the Richard and Rhoda Goldman School of Public Policy, University of California, Berkeley. In the handbook's earliest incarnation, the ideas took form slowly and were conveyed to students in lectures. But because Bardach and his faculty colleagues systematically overloaded their students with work, the students would sometimes skip a lecture-and thus miss out on ideas that he regarded as essential. Bardach determined that if he were to create a handout for the students, at least he would be discharging his responsibility, and it would be up to the students to retrieve the ideas they missed. Over the years, as the handout grew, it was disseminated informally to colleagues at other universities and was posted on the website of the Electronic Hallway, based at the University of Washington. This book is the outgrowth of these previous compilations and the product of many years of experience. Eric M. Patashnik was first exposed to the Eightfold Path when he took the Introductory Policy Analysis course as a student at the Goldman School in the spring of 1988. As a professor, he has assigned earlier editions of Gene's book to hundreds of public policy students at UCLA, the University of Virginia, and Brown University. The presumed user is a beginning practitioner preparing to undertake a policy analysis, such as one of our master's students at Berkeley or Brown. But we have found this handbook useful at both ends of the spectrum-in teaching undergraduate Introduction to Public Policy courses as well as executive education groups. The handbook assumes a familiarity with basic economic concepts, including those having to do with market failures (including market imperfections). It is not meant to stand alone but should be used in conjunction with other sources, including some of the best textbooks in policy analysis, which are cited often to amplify points in this handbook: Behn and Vaupel (1982); Friedman (2002); MacRae and Whittington (1997); Morgan and Henrion (1990); Stokey and Zeckhauser (1978); and Weimer and Vining (2017). A book similar in spirit to this one, and that has many examples drawn from New Zealand and Australia, is Scott and Baehler (2010)"--